In the company of rebels : a generational memoir of bohemians, deep heads, and history makers - Glendinning, Chellis (New Village Press, 2019)
"A personal memoir of encounters with political activist and radical thinkers from the United States and Bolivia, from the 1960s to the present. Describes a life of activism and ideas connected to the themes of ecology, peace, feminism, race and indigenous culture, and social justice."